Renter Power for Better Living: Introduction - Mary N. Harrison (EDIS)
Information in this book will help you protect the health of your family and your financial well-being. It will teach you to care for your home and make it a better place to live. This document is FCS5230-02, one of a series of the Family Youth and Community Sciences Department, UF/IFAS Extension. Original publication date June 2002. Revised December 2005.